TUGAS-TUGAS PERKEMBANGAN ANAK USIA DINI - USMAN, M. (PPs UNJ, 2011)
Stages in the growth and development is marked by the presence of similar characteristics / common traits that appear at nearly the same age period.The existence of similar characteristics in each stage of life was the template for kids, parents and teachers about the skills that must be mastered by children at that age. Within each developmental period in its path, a child should achieve development objectives in accordance with the development period. The whole purpose of development, from early days up until the time is continuous, the achievement of development goals in the previous period became the basis for achieving development goals in the next period. Or in other words, if the purpose of development in the previous period is not achieved by good, feared the achievement of development goals the following term will be disrupted.Keywords: task development, early childhood